Determinants of willingness to pay for the retreatment of insecticide treated mosquito nets in rural area of eastern Ethiopia. Issue 1 (December 2015) - Biadgilign, Sibhatu; Reda, Ayalu; Kedir, Haji
Abstract Objective Is to determine willingness to pay(WTP)/demand for the retreatment of Insecticide treated mosquito nets for malaria control in Ethiopia. Methods A community based cross-sectional study was conducted in Gursum district in Eastern Ethiopia. A total of 335 households were surveyed using a pre-tested structured questionnaire. Multivariable regression analyses using the Tobit model were used to test the theoretical validity of elicited WTP. Results About 159(76.4 %) of them have received a treated insecticide when they obtained. One hundred twenty five (60.4 %) know that the net should be retreated. Around 110(50.7 %), 80(36.9 %) and 27(12.4 %) of the participants feel that the current price of ITNs as negotiable/ not as such expensive, expensive and cheap. About 306(96.5 %) of them reported that they support that ITNs be given freely and 257(82.9 %) were mentioned that the retreatment service should be provided without charge. The WTP amounts ranged from 0 to 10.4 USD. The mean with SD of the respondents from open ended elicitation method for willingness to pay was 1 USD and 1.53 USD. The reduced tobit regression models showed that average income more than 10.4 USD per month and those household who live within a distance in 30 min to the health facility were the determinant for willingness to pay. Conclusion The mean with SD of the respondents for willingness to pay was 1 USD and 1.53 USD. Average monthly income and those household who live within a distance in 30 min to the health facility were determinant for willingness to pay. Government and other development partners should seek a mechanism to make a subsidy or free of charge for the retreatment services. Differential treatment from the public to address the poor and vulnerable households and those who are living far distance from the local health facility is warranted.